Navigating the Nexus: Understanding Socio-Economic Status, Social Isolation, and Depression among Primary Caregivers of Individuals with Physical Disabilities - Abbas, Salbia; Razzaq, Mafia; Shamshaad, Maham; Saeed, Sadia (Pakistan Journal of Humanities and Social Sciences, 2024)
Current Research explored relationship between Socio economic status, Social Isolation and Depression among caregivers of individuals with physical disability. A group of 170 participants was selected using purposive sampling, with occasional utilization of the snowball technique to gather data. The sample included both married and unmarried individuals of both genders. Data collection involved the administration of three scales: the Macarthur SSS scale, comprising 2 items to gauge socioeconomic status; the LSNS, containing 10 items to assess social isolation; and the Hamilton Depression scale, consisting of 21 items to measure depression. Data was analyzed through SPSS. Values of Correlation depicts that there exists a notably weak positive correlation(r=.132, p<0.001) between socioeconomic status and social isolation, alongside a notably strong negative correlation (r=-.413, p<0.001) between socioeconomic status and depression. The significant relationship between depression and the socioeconomic status of caregivers of physically disabled individuals expounds the relationship between caregiving responsibilities, limited opportunities for personal advancement, and heightened risk of psychophysiological ailments due to social isolation and neglect of health. This interconnectedness highlights the need for comprehensive support systems addressing the multifaceted challenges faced by caregivers, to mitigate adverse effects on their well-being and quality of life.